2008
DOI: 10.5194/acpd-8-11997-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intercomparison of aerosol optical depth from Brewer ozone spectrophotometers and CIMEL sunphotometers measurements

Abstract: Abstract. The Langley plot method applied on the Brewer Ozone measurements can provide accurate Aerosol Optical Depth (AOD) in the UV-B. We present seven intercomparisons between AOD retrieved from Brewer Ozone measurements and AOD measured by CIMEL sunphotometer, which are stored in the international AERONET database. Only the intercomparisons between co-located instruments can be used to validate the Langley Plot method applied to the Brewer measurements: in this case, all the correlation coefficient are abo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Aerosol optical depth data are further complemented by UV‐B AOD data (320 nm) derived from Brewer spectrophotometers. The Brewer UV‐B AOD data were evaluated with data from colocated Sun photometers of the AERONET network [ Cheymol et al , 2009].…”
Section: Observational Data For Evaluationmentioning
confidence: 99%
“…Aerosol optical depth data are further complemented by UV‐B AOD data (320 nm) derived from Brewer spectrophotometers. The Brewer UV‐B AOD data were evaluated with data from colocated Sun photometers of the AERONET network [ Cheymol et al , 2009].…”
Section: Observational Data For Evaluationmentioning
confidence: 99%
“…The retrieval of the optical parameters is an important issue of the atmospheric research community (Cheymol et al, 2009). Reuder and Schwander (1999) found that the Single Scattering Albedo, SSA (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 340 and 380 nm is used in the sunphotometer or skyradiometer and even shorter channel 320.1 nm can be used for AOD retrieval in the Brewer spectrophotometer (Kerr, 2002). Several studies verified the quality of AOD measured in these UV-channels by the inter-comparison among different instruments (Cheymol et al, 2009;De Bock et al, 2010). For this study, AOD from UV channel measurements of skyradiometer was also verified with the data measured in the 320.1 nm of Brewer spectrophotometer located in the same site (Koo, 2008).…”
Section: Data Descriptionmentioning
confidence: 98%